Role of Vonoprazan in Helicobacter pylori Eradication Therapy in Japan - Sugimoto, Mitsushige; Yamaoka, Yoshio (Frontiers in Pharmacology, 2019)
Complete eradication of Helicobacter pylori is important for preventing the development of gastric cancer. The outcome of H. pylori eradication therapy is mainly dependent on bacterial susceptibility to antimicrobial agents and potent neutralization of intragastric pH across 24 h, especially when using acid-sensitive antimicrobial agents such as clarithromycin (CLR), amoxicillin and sitafloxacin. However, conventional regimens comprising twice-daily doses (bid) of proton pump inhibitors (PPIs) are generally insufficient for maintaining the required gastric acid secretion for 24 h for successful eradication in all H. pylori-positive patients. Further, the increasing prevalence of CLR-resistant strains with each year has led to a decrease in eradication rates of first-line PPI- and CLR-containing therapies in developed countries, including Japan. In 2015, the potassium-competitive acid blocker vonoprazan (VPZ) became clinically available in Japan. VPZ competitively inhibits H+/K+-ATPase activity more potently than PPIs (e.g., omeprazole, lansoprazole, rabeprazole, pantoprazole, and esomeprazole). Therefore, a VPZ-containing H. pylori eradication regimen is expected to increase the eradication rate compared with conventional regimens containing a standard dose of PPI. In fact, a recent meta-analysis that investigated the efficacy of first-line eradication therapy showed that a VPZ-containing regimen achieved a higher eradication rate than a PPI-containing regimen. While the Maastricht V/Florence Consensus Report recommends selecting a bismuth or non-bismuth quadruple therapy and concomitant therapy for patients living in areas with high prevalence of CLR resistance, a VPZ-containing regimen demonstrates effectiveness for patients infected with CLR-resistant strains and patients living in areas where the prevalence of CLR-resistant strains is >15%. As a next step, studies are needed to determine the factors affecting the clinical outcome of VPZ-containing therapy and optimal VPZ-containing alternative regimens for tailored treatments. In this review, we summarize the advantages and disadvantages of VPZ in H. pylori eradication therapy.